THE IMPACT OF SOCIO-ECONOMIC FACTORS ON THE HEALTH OF THE MOROCCAN IMMIGRANTS IN NAVARRA (SPAIN) - Montoro-Gurich, Carolina (Finisterra, 2019)
This paper explores the relationship between immigration and health status variation among Moroccan immigrants from a gender perspective, using data from a cross-sectional ethnographic survey conducted in the Spanish region of Navarre. Results show, against the literature, that women have a better health status variation than men, probably because men have a higher age profile and a longer stay in Spain. The binary logistic regression reveals important differences in social determinants by gender. Paid employment is the most positive, significant factor for health among women. Close social ties with compatriots, living in an inexpensive old house and, to a lesser extent, having a secondary level of educational achievement are the key factors for men. The economic implications of daily life have an impact on the health of Moroccan immigrants of both sexes.